2017
DOI: 10.1111/jar.12351
|View full text |Cite
|
Sign up to set email alerts
|

Social networks of adults with an intellectual disability from South Asian and White communities in the United Kingdom: A comparison

Abstract: Social networks of individuals with intellectual disability in this study were found to be larger overall in comparison with previous studies, whilst network structure differed between the White and South Asian population. These differences have implications relating to future service planning and appropriateness of available facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…A pilot study, using the adapted SNG, was conducted with two participants with ID and two control participants and found to be reliable and feasible. The SNG has consistently been found to be useful as an instrument to measure social networks (Bhardwaj et al, 2018; Forrester-Jones et al, 2004, 2006, 2012, 2018; Sango and Forrester-Jones, 2017). The Cronbach’s α for the adapted SNG was 0.96 for all 47 items.…”
Section: Methodsmentioning
confidence: 99%
“…A pilot study, using the adapted SNG, was conducted with two participants with ID and two control participants and found to be reliable and feasible. The SNG has consistently been found to be useful as an instrument to measure social networks (Bhardwaj et al, 2018; Forrester-Jones et al, 2004, 2006, 2012, 2018; Sango and Forrester-Jones, 2017). The Cronbach’s α for the adapted SNG was 0.96 for all 47 items.…”
Section: Methodsmentioning
confidence: 99%
“…Adapted from Tracy and Abell (), it maps the structural size, membership, density (i.e., the proportion of network members who are interconnected; Brugha et al., , p. 124), interactional (i.e., reciprocity, frequency, duration and closeness) and supportive (i.e., companionships and decision making) components of individual's networks. A fuller version of the SNG (Bhardwaj, Forrester‐Jones, & Murphy, in press; Forrester‐Jones et al., ; 2012) is published elsewhere (Forrester‐Jones & Broadhurst,).…”
Section: Methodsmentioning
confidence: 99%
“…In Dagnan & Ruddick's, 1997 study, where mean network size was 3.1 members, the authors suggested that low numbers of non-disabled people in networks could be as a result of only recently moving from an institutional setting. In the most recent quantitative study, Bhardwaj et al (2018) found the same three groups made up the bulk of adults' networks, with higher than average network size possibly linked to health, age and level of socially inclusive activities. Network size in all studies though remained significantly lower and less diverse than non-disabled people's networks.…”
Section: Network Size and Characteristicsmentioning
confidence: 99%
“…Social network size for adults with intellectual disabilities however is smaller and more restricted; Forrester-Jones et al, (2006) in their study of 213 individuals, finding an average network size of just 22 contacts and 'dense' network membership restricted to mainly other adults using intellectual disability services. Social networks are key to social identity for adults with intellectual disabilities (Heyman et al, 1997) and social networks are vital for social functioning, self-esteem and quality of life (Bhardwaj, Forrester-Jones & Murphy, 2018). Social networks are also associated with happiness, self-confidence, mental health and leisure activities (Forrester-Jones et al, 2006) and are deemed crucial for facilitating social inclusion (van Asselt-Goverts et al, 2013;White & Forrester-Jones, 2019).…”
mentioning
confidence: 99%